KEPASTIAN HUKUM EKSEKUSI JAMINAN FIDUSIA TANPA MELALUI PUTUSAN PENGADILAN TERHADAP OBJEK JAMINAN YANG TIDAK DISERAHKAN SECARA SUKARELA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 2/PUU-XIX/2021 - Rahmansyah, Fuad; Maryano, Maryano; TW, Gatut Hendro (SINERGI : Jurnal Riset Ilmiah, 2025)
The objectives of this thesis research are: 1) To analyze the execution of fiducia security without a court ruling when the debtor does not voluntarily surrender the collateral object after Constitutional Court Ruling Number 2/PUU-XIX/2021. 2) To analyze the legal certainty for creditors against potential losses arising from the forced execution of fiducia security without a court ruling after Constitutional Court Ruling Number 2/PUU-XIX/202. This study emphasizes the theories of legal certainty and contract law.The research method used is normative juridical research, which involves studying literature or secondary data as the primary source. This is done by conducting a search on the researched issues. The results of this thesis research are: 1) The execution of fiducia security without a court ruling when the debtor does not voluntarily surrender the collateral object after Constitutional Court Ruling Number 2/PUU-XIX/2021 substantially weakens the execution rights for creditors. The researcher argues that the ruling is based on a mistaken and inconsistent understanding of fiducia legal concepts. The researcher asserts that the execution of fiducia security, whether through parate executie or the Implementation of an Executorial Title, is essentially a coercive action to fulfill a defaulting debtor's obligations. The Constitutional Court's ruling, which redefines parate executie as "voluntary execution" (only possible if the debtor voluntarily surrenders the collateral), is considered non-operational and contradicts the very essence of execution. The researcher highlights the ambiguity in the court's reasoning, which equates the Implementation of an Executorial Title (which should be carried out by a court) with parate executie (carried out by the creditor). The researcher argues that parate executie should be the primary option for its efficiency, while the Implementation of an Executorial Title serves as an "emergency door" if parate executie fails. By eliminating parate executie as a coercive action, creditors lose a fast, effective, and efficient execution mechanism. This creates a loophole for debtors acting in bad faith to delay payments, causing financial losses for creditors. 2) Regarding legal certainty for creditors against potential losses from the forced execution of fiducia security without a court ruling after Constitutional Court Ruling Number 2/PUU-XIX/202, the researcher argues that while a court ruling has binding legal force (res judicata pro veritate habetur), it must be based on strong legal logic, not just formal validity. The researcher rejects the legalistic paradigm and emphasizes the importance of judges examining essential legal norms and principles, such as the principle of good faith, to ensure substantial justice and prevent arbitrary actions. This Constitutional Court ruling significantly harms creditors by removing parate executie (direct execution) as a coercive measure. The ruling requires that execution can only be carried out if the debtor acknowledges default and voluntarily surrenders the collateral. Otherwise, execution must go through the courts, which contradicts the spirit of efficiency in the Fiducia Security Law. The researcher confirms that the correct concept is the transfer of ownership as collateral (proforma or fiction), which is protected by the verval beding principle (Article 33 of the Fiducia Security Law) that prohibits the full transfer of ownership upon default. This error makes the court's argument about the debtor being in a "state of not being completely free" irrelevant. As a result of this ruling, creditors lose their right to a quick and efficient execution. Debtors acting in bad faith can exploit this legal loophole to delay payments or even abscond with the collateral, causing greater financial losses for creditors. This undermines the principle of easy-to-execute collateral and creates an imbalance that is detrimental to creditors.